Budget Refocusing Analysis for Prevention and Handling of Corona Virus Disease 2019 (Covid-19) at the Health Office of Sigi District - Nur Afni; Muhamad Andri (International Journal of Health, Economics, and Social Sciences (IJHESS), 2022)
This study aims to determine the process of budget refocusing in the context of preventing and handling COVID-19 in the Sigi Regency. The type of research used is qualitative research. The data sources in this study are primary and secondary data sources with a total of 7 (seven) informants. Data collection techniques use the method of observation, interviews, and documentation. The result of this research is that the refocusing of the COVID-19 budget in Sigi Regency has been carried out based on Presidential Instruction (Inpres) No. 4 of 2020 concerning refocusing activities and having an impact on the achievement of national priority programs/activities and the vision and mission of regional heads that do not reach the target. The refocusing of the COVID-19 budget in the Sigi Regency was sourced from the General Allocation Fund (DAU), the Special Allocation Fund (DAK), and the Regional Incentive Fund (DID). The budget refocusing process is carried out on a bottom-up basis, where the puskesmas propose a budget based on cases in the work area, which the Sub then verifies. The planning coordinator for the Health Office will then be discussed and approved by the Regional Revenue Budget Team (TAPD).